Alternating atrial and ventricular tachycardia. Issue 6 (June 1979) - Jordan, R M; McAnulty, J H; Ritzmann, L
Abstract : A patient with alternating atrial and ventricular tachycardia is described. He had an acute myocardial infarction and was taking digitalis. The atrial tachycardia, which was occasionally associated with aberrant ventricular conduction, was able to interrupt the ventricular tachycardia though the reverse was not true, suggesting a retrograde conduction block. This patient shows that atrial and ventricular arrhythmias can alternate and, since tachycardia with aberrant ventricular conduction can closely resemble ventricular tachycardia, intra-atrial electrocardiography may be necessary to establish an accurate diagnosis.